Gallblader Ultrasound Examination Technique In Clinical Hydrops Gallblader At Radiology Installation Of Banten Hospital - Fukuyama Trisnadi, Ceanave (Syntax Corporation Indonesia, 2024)
Gallbladder hydrops is a pathological enlargement of the gallbladder that is usually caused by obstruction of the bile duct. Rapid and accurate diagnosis is essential to prevent further complications. Ultrasonography (USG) is one of the effective non-invasive imaging methods to detect this condition. This study aims to describe the gallbladder USG examination technique in cases of gallbladder hydrops at the Radiology Installation of Banten Regional Hospital. This study uses a descriptive method based on the results of real work practices (PKN). The results show that USG examination with a C5-1 transducer in the supine position is effective in identifying gallbladder distension, the presence of stones, and wall thickening. Patient preparation techniques such as fasting for 6 hours before the examination are also important to increase diagnostic accuracy.